Interaction of Silver-Lignin Nanoparticles With Mammalian Mimetic Membranes - Hoyo, Javier; Ivanova, Kristina; Torrent-Burgues, Juan; Tzanov, Tzanko (Frontiers in Bioengineering and Biotechnology, 2020)
Silver nanoparticles (AgNPs) have broad spectrum antibacterial activity, but their toxicity to human cells has raised concerns related to their use as disinfectants or coatings of medically relevant surfaces. To address this issue, NPs comprising intrinsically bactericidal and biocompatible biopolymer and Ag with high antibacterial efficacy against common pathogens and compatibility to human cells have been engineered. However, the reason for their lower toxicity compared to AgNPs has not yet been elucidated. This work studies the in vitro interaction of AgLNPs with model mammalian membranes through two approaches: i) Langmuir films and ii) supported planar bilayers studied by quartz crystal microbalance and atomic force spectroscopy. These approaches elucidate the interactions of AgLNPs with the model membranes indicating a prominent effect of the bioresourced lignin to facilitate the binding of AgLNPs to the mammalian membrane, without penetrating through it. This study opens a new avenue for engineering of hybrid antimicrobial biopolymer –Ag or other metal NPs with improved bactericidal effect whereas maintaining good biocompatibility.